The Implementation of Emancipated Curriculum: Teachers’ Strategies in Teaching English Writing - Leny Kicha; Nihta Vera Frelly Liando; Tini Mogea (Universitas Muhammadiyah Enrekang, 2024)
The curriculum significantly influences the direction of classroom learning activities. In an era where adapting to rapid change is essential, the Kurikulum Merdeka (emancipated curriculum) has been introduced to address educational needs. This article explores how teachers implement strategies for teaching English writing based on the emancipated curriculum, along with the challenges they encounter. The research involved two English teachers from Islamic junior high schools, both teaching seventh graders. Data was gathered through interviews, observations, and documentation. The findings revealed that students were highly engaged in English writing due to the teaching strategies employed, making the learning experience more enjoyable and engaging. In the application of the emancipated curriculum, teachers acted primarily as facilitators, guiding students to take a more active role in their learning. The study suggests that the teachers' strategies were well-suited to the students' abilities and learning needs.